2021
DOI: 10.3727/096504021x16184815905096
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Early Outcomes of Combined Chemotherapy With Arsenic Trioxide for Stage 4/M Neuroblastoma in Children: A Multicenter Nonrandomized Controlled Trial

Abstract: This nonrandomized, multi center cohort, open label clinical trial evaluated theefficacy and safety of combined chemotherapy with arsenic trioxide (ATO) in childrenwith stage 4/M neuroblastoma (NB). We enrolled patients who were newly diagnosedwith NB and assessed as stage 4/M and received either traditional chemotherapy or ATOcombined with chemotherapy according to their own wishes. Twenty two patients wereenrolled i n the trial group (ATO combined with chemotherapy) and thirteen patientswere enrolled in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Preliminary results are encouraging. 36 Of the 22 patients in the trial group and 13 in the control group, we found that patients who received ATO combined with chemotherapy had a significantly higher response rate than those who treated with traditional chemotherapy (objective response rate (ORR): 86.36% vs 46.16%, P = .020). Reversible cardiotoxicity was just observed in 3 patients who were treated with ATO and no other differential adverse events were observed between 2 groups.…”
Section: Discussionmentioning
confidence: 83%
“…Preliminary results are encouraging. 36 Of the 22 patients in the trial group and 13 in the control group, we found that patients who received ATO combined with chemotherapy had a significantly higher response rate than those who treated with traditional chemotherapy (objective response rate (ORR): 86.36% vs 46.16%, P = .020). Reversible cardiotoxicity was just observed in 3 patients who were treated with ATO and no other differential adverse events were observed between 2 groups.…”
Section: Discussionmentioning
confidence: 83%
“…revealed that the combination of ATO and (131)I‐MIBG for the treatment of relapsed or refractory stage 4 NB or metastatic pheochromocytoma did not yield a higher response rate compared to the use of single‐agent (131)I‐MIBG, despite the patients' favorable tolerance of the therapy 36 . In contrast, our multicenter non‐randomized controlled clinical study has provided evidence that the combination of ATO and chemotherapy, in comparison to conventional chemotherapy, could significantly enhance the objective remission rate (89.74% vs. 46.15%) and CR (69.23% vs. 23.08%) in patients with HR‐NB, while also being well‐tolerated 29 …”
Section: Discussionmentioning
confidence: 84%
“…Moreover, subsequent clinical trials have provided further evidence that the combination of ATO and chemotherapy substantially improves complete response (CR) rates for patients with HR-NB, whereas concurrently maintaining a favorable safety profile. 28,29 Additionally, a previous study by our research team uncovered a substantial enrichment of differential proteins within the ferroptosis pathway subsequent to the administration of ATO to NB cell lines, as evidenced by off-label quantitative proteomics methodologies. Notably, the expression of GPX4, a crucial rate-limiting enzyme closely associated with the ferroptosis pathway, was markedly reduced.…”
Section: How Might This Change Clinical Pharmacology or Translational...mentioning
confidence: 88%
See 2 more Smart Citations